2014
DOI: 10.1007/s00438-014-0869-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique

Abstract: in two other genes decreased, the sites of methylation remained, and the expression increased only slightly. All of these results suggested that drought stress decreased the total DNA methylation level in perennial ryegrass and demethylation up-regulated related gene expressions and that the extent of methylation was negatively correlated with expression. Overall, the induced epigenetic changes in genome probably are an important regulatory mechanism for acclimating perennial ryegrass to drought and possibly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 56 publications
5
56
1
Order By: Relevance
“…Here, the MYB transcriptional factor gene might be induced and demethylated by the disease, leading to its higher expression level with the adaption of continuous monoculture from R. glutinosa roots. Previous reports showed that transposons were the changes in methylation status during plant the stress (Boyko and Kovalchuk, 2008;Tang et al, 2014). Here the up-regulation of a retrotransposon in the R2 material coincided with its demethylated status.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Here, the MYB transcriptional factor gene might be induced and demethylated by the disease, leading to its higher expression level with the adaption of continuous monoculture from R. glutinosa roots. Previous reports showed that transposons were the changes in methylation status during plant the stress (Boyko and Kovalchuk, 2008;Tang et al, 2014). Here the up-regulation of a retrotransposon in the R2 material coincided with its demethylated status.…”
Section: Discussionmentioning
confidence: 53%
“…Here the up-regulation of a retrotransposon in the R2 material coincided with its demethylated status. Activated transposons could reshape the R. glutinosa root transcriptome by demethylating (and hence up-regulating) other genes as previously described (Boyko and Kovalchuk, 2008;Tang et al, 2014). In addition, a demethylated gene encoding a SWR1 complex subunit 6, which involved in plant flower development processes (Hurtado et al, 2006), was over-expressed in the R2 roots, promoting continuous monocultured R. glutinosa earlier flowering.…”
Section: Discussionmentioning
confidence: 63%
“…We previously showed that perennial ryegrass has high levels of genomic methylation (over 50%), which decrease by 10% when exposed to drought conditions (Tang et al, 2014b). Furthermore, we also characterized genes that respond to heat or cold stress in perennial ryegrass (Wang et al, 2015b), and found that high number of P450 s (cytochrome P450, CYP) showed significant change in gene expression under heat and cold stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are similar to previous reports showing decrease in DNA methylation upon stress treatment. Drought treatment of perennial ryegrass leads to reduced methylation levels ( Tang et al, 2014a), and salt stress treatment of tobacco plants leads to demethylation of genes in the flavonoid biosynthetic and antioxidative pathways (Bharti et al, 2015). In barley (Hordeum vulgare), water-deficiency induced DNA methylation changes preferentially occur within the gene bodies rather than the promoter regions (Chwialkowska et al, 2016).…”
Section: The Response Of Lpcyp72a161 Under Temperature Stressesmentioning
confidence: 99%
See 1 more Smart Citation